Формирование и усиление импульса длительностью 50 пс в лазерной системе THL-100; Квантовая электроника; Т. 47, № 3 - Алексеев С. В. Сергей Владимирович; Иванов Н. Г. Николай Георгиевич; Иванов М. В. Михаил Владимирович; Лосев В. Ф. Валерий Федорович; Месяц Г. А. Геннадий Андреевич; Михеев Л. Д. Леонид Дмитриевич; Панченко Ю. Н. Юрий Николаевич; Ратахин Н. А. Николай Александрович; Ястремский А. Г. Аркадий Григорьевич (2017, 2017)
Заглавие с экрана